Advancements in Structural Basis of Covalent Inhibitors Targeting SARS-CoV-2 Essential Proteins - Fatima, Israr; Alshabrmi, Fahad M.; Alkhayl, Faris F. Aba; Qasim, Muhammad; Shafqat, Almera; Batool, Sara; Jawad, Muhammad; Qamar, Muhammad Tahir Ul; Rehman, Abdur (Current Medicinal Chemistry, 2025)
Covalent inhibitors play a pivotal role in the development of pharmaceutical therapies, as they form stable, irreversible bonds with target biomolecules, leading to prolonged therapeutic effects and enhanced efficacy. Since covalent inhibitors first appeared in the late 1800s, the field has become innovative rapidly, and covalent inhibitors now account for around 30% of all marketed therapeutics. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the pandemic of Coronavirus Disease 2019 (COVID-19). SARS-CoV-2 needs to be cured with a medicine that is beneficial and with the least side effects. It is necessary to formulate drug candidates to treat this pathogen. The predominance of covalent medications will be briefly discussed in this review, followed by an introduction to their methods of action, as well as more thorough discussions of the safe and effective covalent enzyme inhibitors against SARS-CoV-2. Our main concern is to study covalent inhibitors which are mainly involved in blocking the viral entry of the virus SARS-CoV-2 into the host cell along with its replication and translation process. In the development of anti-SARS-CoV-2 medicines researchers can use those reported drugs as prospective candidates.
Keywords: covalent inhibitors